How Do Light and Intermittent Smokers Differ from Heavy Smokers in Young Adulthood: The Role of Smoking Restraint Strategies. Issue 3 (26th May 2016) - Thrul, Johannes; Ferguson, Stuart G.; Bühler, Anneke
ABSTRACT: Light and intermittent smoking has become a prevalent pattern of use among young adults. Little is known about which factors differentiate light and intermittent smokers (LITS) from heavy smokers (HS) in young adulthood. In this study, we compare young adult LITS with HS with regard to demographic- and smoking-related variables, self-control abilities, and concrete strategies of smoking restraint. The data were collected as part of an Ecological Momentary Assessment (EMA) study with 137 German young adult smokers (M Age = 21.1 years, 46.0% female; 76 HS [≥10 cigarettes/day] and 61 LITS [≤5 cigarettes/day]). Participants were recruited over the Internet and completed a baseline questionnaire online. Several variables differentiated LITS and HS in a multiple logistic regression analysis: LITS reported fewer smoking friends (p < .001) and a higher self-efficacy to resist smoking (p < .01). Further, LITS smoking status was associated with reporting a past quit attempt (p < .05) and the use of smoking restraint strategies (counting, limiting, and purposefully not smoking cigarettes; p < .05). Notably, nicotine dependence and trait self-control abilities did not differentiate between LITS and HS. Our results point to the role of smoking restraint strategies and self-monitoring of smoking to limit the daily number of cigarettes smoked.